Development of a technology to produce titanium powder with a low carbon footprint - Gonchar, Andrii; Troshchylo, Viktor; Brodskyy, Andriy; Yarovynskyi, Volodymyr; Chukhmanov, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2023)
This paper reports the analysis of modern technologies for the production of titanium from oxide raw materials. It has been established that current industrial methods for producing titanium require the use of carbon as a reducing agent and, accordingly, cannot decrease carbon emissions without changing the technology. That is why devising a technology for producing titanium with a reduction in emissions of carbon components is a relevant task. So, the object of research is the technology of obtaining titanium from its oxide without the use of carbon components. It was found that an integrated approach to the preparation of raw materials and the separation of reduction processes with the successive use of two types of reducing agents – magnesium and calcium, made it possible to create an effective process for producing titanium without the use of carbon reducing agents. The influence of calcium and magnesium chlorides as promoters of the reduction process was revealed. Experimental studies have established that the shape and density of raw materials significantly affect the efficiency of the reduction process by streamlining the reducing agent flows and reaction products in the furnace charge. The established regularities made it possible to improve the process of reduction of titanium oxide to obtain samples of titanium powders with an oxygen content of 0.17 %, which corresponds to international standards for titanium alloys and powders. Additional plasma treatment made it possible to obtain materials that were suitable for additive processes in all respects. A systematic approach to the utilization of reaction products made it possible to devise a technological scheme in which all possible waste is either returned to the technological process after treatment or processed into marketable products. Based on the results of the study, a technological scheme for obtaining powders of titanium alloys from titanium oxide by complex reduction in two stages – magnesium and calcium – was developed. The proposed scheme involves standard metallurgical processes and is brought to standard processes and equipment of metallurgical enterprises and chemical industry. In terms of practical significance, the results of this work could be used in the development of industrial technology to produce titanium from titanium dioxide without the use of carbon components.